A century of victimhood: Antecedents and current impacts of perceived suffering in World War I across Europe. (7th June 2017) - Bouchat, Pierre; Licata, Laurent; Rosoux, Valérie; Allesch, Christian; Ammerer, Heinrich; Bovina, Inna; Bruckmüller, Susanne; Cabecinhas, Rosa; Chryssochoou, Xenia; Cohrs, J. Christopher; Csertő, István; Delouvée, Sylvain; et al.
Abstract: The present study addresses antecedents and consequences of collective victimhood in the context of World War I (WWI) across 15 European nations ( N  = 2423 social science students). Using multilevel analysis, we find evidence that collective victimhood is still present a hundred years after the onset of the war and can be predicted by WWI‐related objective indicators of victimization at national and family levels. This suggests that collective victimhood is partly grounded in the actual experience of WWI. In addition, we show that sense of collective victimhood positively predicts acknowledgment of the suffering inflicted by one's nation on other countries during WWI. This is consistent with a social representation of WWI as involving a vast massacre in which nations were both victim and perpetrator. Finally, we find that objective indicators of victimization predict pacifism in divergent ways, with an indicator at the national level associated with more pacifist attitudes and an indicator at the family level being associated with less pacifist attitudes. This finding suggests that war‐torn societies may have developed social representations favouring peaceful coexistence whereas, at the family level, victimization may still foster retaliatory tendencies.